An Early Stage Electrochemical Evaluation of Ovarian Cancer: α-MnO2 Nanorod and AuNP Hybrid Nanoarchitectures - Dezhakam, Ehsan; Dehghani, Sarina; Faraghi Vayghan, Roya; Naseri, Abdolhossein; Khalilzadeh, Balal; Isildak, Ibrahim (AMER CHEMICAL SOC, 2025)
Ovarian cancer (OC), a predominant contributor to fatalities among gynecologic cancers, necessitates early detection for effective treatment. The inadequate sensitivity of current diagnostic methods urged us to develop a label-free electrochemical biosensor for the timely diagnosis of OC. This biosensor utilizes alpha-MnO2 nanorods (alpha-MnO2NRs) decorated with gold nanoparticles (AuNPs) to enhance conductivity and sensitivity. alpha-MnO2NRs, offering a large surface area, are electrodeposited onto a glassy carbon electrode (GCE), followed by decoration with AuNPs. Both electrodeposition steps were carried out by the chronoamperometry (CHA) technique. The characteristics of the nanomaterials were evaluated through XRD, SEM, and EDX methods. The biodetection mechanism involves the immobilization of the biotinylated monoclonal CA125 antibody, followed by MCH drop-casting and further incubation with the CA125 antigen. The electrochemical assessments were conducted by employing the differential pulse voltammetry (DPV) method. The developed biosensor demonstrated a dynamic linear range for CA125 detection (10-70 nanounits/mL), a low limit of detection (LOD = 9.82 nanounits/mL), excellent repeatability, and reproducibility. Clinical serum sample analysis validated its practical application, highlighting its potential for improving patient outcomes. The use of screen-printed electrodes (SPCEs) not only simplifies the fabrication process but also increases its suitability for point-of-care diagnostics, offering a portable solution for real-time monitoring. This robust and sensitive biosensing platform shows great promise for clinical diagnostics and biomedical research.
Keywords: ULTRASENSITIVE DETECTION; NANOPARTICLES; BIOSENSOR; ELECTROOXIDATION; OXIDATION; DOPAMINE; SENSOR; GREEN; Chemistry; Materials Science